2007
DOI: 10.2135/cropsci2005.12.0453
|View full text |Cite
|
Sign up to set email alerts
|

Trinexapac‐ethyl and Paclobutrazol Affect Kentucky Bluegrass Single‐Leaf Carbon Exchange Rates and Plant Growth

Abstract: Trinexapac‐ethyl (TE) [4‐(cyclopropyl‐α‐hydroxy‐methylene)‐3,5‐dioxocyclohexanecarboxylic acid ethyl ester] and paclobutrazol (PAC) [(2RS,3RS)‐1‐(4‐chlorophenyl)‐4,4‐dimethyl‐2‐(1H‐1,2,4‐triazol‐1‐yl)pentan‐3‐ol] are routinely used to suppress clipping production. Single‐leaf turfgrass C exchange rates (CERs) in response to plant growth regulator (PGR) treatment have not been characterized. Individual Kentucky bluegrass (KBG, Poa pratensis L.) plants received label rates of TE or PAC and were placed in growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 28 publications
(37 reference statements)
1
13
0
Order By: Relevance
“…Inhibition of GA 1 due to TE action restricts leaf cell elongation and increases cell density, resulting in more chlorophyll per unit area and darker green leaves (Ervin and Koski, 2001; Heckman et al, 2005; McCullough et al, 2006). One would assume that increased chlorophyll concentration would be associated with increased efficiency of light capture in PSII, but Beasley and Branham (2007) reported no change in Kentucky bluegrass single‐leaf PE due to a single application of TE. However, results of repeated TE applications to field‐maintained creeping bentgrass (Zhang and Schmidt, 2000) and the species in the study herein indicate that PE (when measured on a canopy, rather than a single‐leaf basis) was consistently higher relative to the untreated species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of GA 1 due to TE action restricts leaf cell elongation and increases cell density, resulting in more chlorophyll per unit area and darker green leaves (Ervin and Koski, 2001; Heckman et al, 2005; McCullough et al, 2006). One would assume that increased chlorophyll concentration would be associated with increased efficiency of light capture in PSII, but Beasley and Branham (2007) reported no change in Kentucky bluegrass single‐leaf PE due to a single application of TE. However, results of repeated TE applications to field‐maintained creeping bentgrass (Zhang and Schmidt, 2000) and the species in the study herein indicate that PE (when measured on a canopy, rather than a single‐leaf basis) was consistently higher relative to the untreated species.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of cell elongation has been shown to increase mesophyll cell density and chlorophyll concentration, resulting in dwarfed shoots that are darker green (Ervin and Koski, 2001; Heckman et al, 2005; McCullough et al, 2006). Net photosynthesis may be increased by TE as photosynthetic rates are reportedly unchanged due to TE on cool‐season (Stier et al, 1997; Beasley and Branham, 2007) and warm‐season (Qian et al, 1998) turfgrasses, while maintenance respiration may be decreased (Heckman et al, 2001). Photosynthate not used for leaf elongation must be stored or transported to other organs for growth and maintenance.…”
mentioning
confidence: 99%
“…Operational procedures were similar to those outlined in Beasley and Branham (2007) except that roots were stored at 4°C and placed in water during the analysis rather than a ethanol and deionized water solution, the exclusion fi lter in this study was set to 0.15 mm rather 0.25 mm, and the scanner was confi gured to 600 dpi rather than 500 dpi. Three techniques were used to quantify creeping bentgrass root development in this research: visual assessments of root length, measurements of root architecture with the WinRhizo Pro system (Regent Instruments Inc., Quebec City, QC), and ashing.…”
Section: Parameters Evaluatedmentioning
confidence: 99%
“…Temperature has been reported to affect TE efficacy on hybrid bermudagrass and Kentucky bluegrass ( Poa pratensis L.) (Lickfeldt et al, 2001; Fagerness et al, 2002; Beasley and Branham, 2007; Beasley et al, 2007). Fagerness et al (2002) showed that TE provided greater growth suppression duration and magnitude of ‘Tifway’ bermudagrass at 20/10°C day/night air temperatures as opposed to 35/25°C.…”
mentioning
confidence: 99%